Perancangan Interior “Do It Yourself” Cake Shop and Café di Surabaya - Evelyn Fifilia Tjahjono; I Gusti Ngurah Ardana; Grace Mulyono (Intra, 2016)
Cake is one of the popular dessert which is loved by most people, regardless of age. Cake Shop and Café, is one of the place that facilitate the needs of the community. However, in this globalization era, custom cake is more favored by the people. The cake that just traded in mediocre, can lose interest so this business becomes less developed. So, based on that facts, “Do It Yourself” Cake Shop and Café is designed in Surabaya as a form of reaction to respond the demands of society in this era. The problem in this design can be solved by the application of the concept of fun and togetherness, because this facility provides a pleasant atmosphere and foster the spirit of togetherness. The design is processed using the method of literature, interview, and documentation. The data that has been collected were analyzed with descriptive and comparative method, and simple statistics, because this research is included with quantitative data, related to some elements of interior design. This design is provided with conventional cake trade, recreational facility to decorate their own cake, relaxation and education facility such as baking class, seminar area and exhibition area.